DETECÇÃO E ANÁLISE DE LESÕES DO PERIÁPICE EM RADIOGRAFIAS PERIAPICAIS (REMUNOM, 2025)
The study aimed to determine the prevalence of periapical lesions in relation to the dental arches and to correlate the occurrence of these lesions in non-endodontically treated teeth and teeth that had undergone endodontic intervention. To achieve this, an observational and cross-sectional study was conducted using imaging exams obtained during the screening consultation at the dental clinic of a public university in Belém throughout 2022 and the first semester of 2023. A total of 4,492 imaging exams were analyzed, of which 4,423 were excluded, resulting in a final sample of 95 exams. From these exams, information on patients, including gender and age, was collected, as well as the characterization of the lesions based on their contour (regular or irregular). The evaluator's calibration was verified using the Kappa coefficient. For data processing, the Jamovi software (version 1.1.9; Oxford, United Kingdom) and Excel were used.